Assessing e-commerce adoption by small and medium enterprises in Malaysia, Singapore and Thailand - Nezakati, Hossein; Jofreh, Manouchehr; Leong, Gary Wai Liong; Asgari, Omid (IDOSI Publications, 2012)
Many publications to date, have describe the various adoption of e-commerce among firms small and large. However, although the e-commerce adoption growth has been significant, the e-commerce adoption rate among SMEs has mainly been among the industrialized countries. First objective of this research is to assess the usefulness and ease of using e-commerce perceived by SMEs in both service and manufacturing industries whether there are significant differences between Malaysia, Singapore and Thailand respectively. The second objective is to assess the important technical competencies in terms of technical knowledge and skills in e-commerce setup in both service and manufacturing industry across and to identify whether are there significant difference between Malaysia, Singapore and Thailand. The relationship among variables has been studied through correlation test. Three dimensions have been analyzed. Technical knowledge related to e-commerce, perceive ease of use of e-commerce and perceive usefulness of e-commerce. From the statistical data analysis output, it is found that technical knowledge related to e-commerce is not significantly different between the countries in both the manufacturing and the service industry but both the manufacturing and service industry reckons that technical knowledge and skill poses to biggest challenge that effect the uptake of e-commerce similarly across the three countries.